KONTEKS POLITIS ADMINISTRATIF DALAM REFORMASI PELAYANAN PUBLIK DI DAERAH - Syamsul Ma’arif (Yogyakarta State University, 2013)
Public service is area where government and large society meet one another. Unfortunatelly, public service in Indonesia is still contaminated by various practices of corruption. Based on the such objective condition, war against corruption should be done not only by using repressive approach like law enforcement. This action, however, needs to be supported by preventive approach through public service reforms. By conducting public service reforms, government attempts to make social welfare of the people become higher by delivering acces of resources alocation (politics, social, and economics) as wide as possible for the people. Thus, the issue of public service reforms should be positioned as part of common efford to solve problems of justice, redistribution, and choice of development model. Public service reforms finally must be understood not just administratve affair, but also political affair.Key word: public service, corruption, reforms